The Effectiveness of Pairwork Activities Technique on Writing Ability of Students in Vocational School - Hermi Zaswita; Rodiyal Ihsan (Indonesian TESOL Journal, 2019)
This study is aimed at finding out the effectiveness of pairwork activities technique on students’ writing ability. The research is quasi-experiment with posttest only design. Students at grade XI Vocational School 1 Sungai Penuh engage in the study, whereas only two classes selected as sample (experimental class and control class). Writing test carries out after the treatment in each class, it means instrument is constructed in writing form in order to know students ability in writing. The data are analyzed by using t-test. The finding of hypotheses testing proves that the p-value is 0,00. Thus, p-value is lower than 0,05 (0,00<0,05) which means H0 is rejected and H1 is accepted. Hence, the pairwork activities technique is effective to be used in creating student’s better writing ability than conventional technique. Pairwork activities technique can enhance students activities in writing, where each pair of students should be active in generousing the ideas and cross-check their own writing with the intention of create better writing outcome.